MANAJEMEN KURIKULUM SMK BIDANG OTOMOTIF DALAM MENGHADAPI PERKEMBANGAN TEKNOLOGI MODERN - Meiyaldi Eka Putra; Hasan Maksum; Waskito (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
Abstract: The development of modern technology in the automotive industry, such as electric vehicles, hybrid vehicles, Advanced Driver Assistance Systems (ADAS), the Internet of Things (IoT), artificial intelligence, and digital manufacturing, requires Vocational High Schools (SMK) to continuously adjust their curriculum. This study aims to analyze the management of SMK automotive curriculum in facing modern technological developments. The research method used is library research with a qualitative descriptive approach through the analysis of various literature, educational policies, scientific journals, and documents related to vocational education. The results of the study indicate that the success of automotive curriculum management is determined by four main management functions, namely planning, organizing, implementing, and evaluating the curriculum. The integration of modern technology into the curriculum requires industry involvement, improving teacher competency, providing technology-based infrastructure, and implementing project-based learning and Teaching Factory. An adaptive and flexible curriculum can increase the relevance of graduate competencies to the needs of the workforce. Therefore, synergy between schools, government, industry, and universities is a crucial factor in realizing automotive vocational education that is responsive to modern technological developments. Keywords: Curriculum Management, Automotive Vocational School, Modern Technology, Vocational Education, Automotive Industry.   Abstrak: Perkembangan teknologi modern pada industri otomotif, seperti kendaraan listrik, kendaraan hibrida, sistem Advanced Driver Assistance Systems (ADAS), Internet of Things (IoT), kecerdasan buatan, dan digitalisasi manufaktur, menuntut Sekolah Menengah Kejuruan (SMK) untuk melakukan penyesuaian kurikulum secara berkelanjutan. Penelitian ini bertujuan untuk menganalisis manajemen kurikulum SMK bidang otomotif dalam menghadapi perkembangan teknologi modern. Metode penelitian yang digunakan adalah studi kepustakaan (library research) dengan pendekatan deskriptif kualitatif melalui analisis berbagai literatur, kebijakan pendidikan, jurnal ilmiah, dan dokumen terkait pendidikan vokasi. Hasil kajian menunjukkan bahwa keberhasilan manajemen kurikulum otomotif ditentukan oleh empat fungsi utama manajemen, yaitu perencanaan, pengorganisasian, pelaksanaan, dan evaluasi kurikulum. Integrasi teknologi modern ke dalam kurikulum memerlukan keterlibatan industri, peningkatan kompetensi guru, penyediaan sarana-prasarana berbasis teknologi, serta penerapan pembelajaran berbasis proyek dan Teaching Factory. Kurikulum yang adaptif dan fleksibel mampu meningkatkan relevansi kompetensi lulusan terhadap kebutuhan dunia kerja. Oleh karena itu, sinergi antara sekolah, pemerintah, industri, dan perguruan tinggi menjadi faktor penting dalam mewujudkan pendidikan vokasi otomotif yang responsif terhadap perkembangan teknologi modern. Kata Kunci: Manajemen Kurikulum, SMK Otomotif, Teknologi Modern, Pendidikan Vokasi, Industri Otomotif.